Decision-making of corporate clients during strategic briefing process according to knowledge acquisition types - Yu, Chan-Suk; Kim, Ju-Hyung (Journal of Civil Engineering and Management, 2025)
Organizational clients with limited experience in strategic briefing often face challenges in identifying building project outcomes for achieving a competitive edge in their business. Communication with practitioners during strategic briefing facilitates clients in acknowledging the importance of timely decision-making and being involved in a knowledge spiral to acquire the information. Knowledge-acquisition by clients can lead to behavioral changes, both within themselves and their organizations. This study classifies knowledge-acquisition types (KATs) and investigates the potential for rational decision-making in briefings. A framework, developed through a literature review and practical insights, is validated by introducing the Action Research approach with stakeholders across ten building projects in sectors: manufacturing, retail, and public enterprises. The framework, refined during interactions among researchers, clients and service providers, identifies KAT1 as the domain knowledge, KAT2 as the administrative knowledge, and KAT3 is the facility knowledge of clients. KAT4, the difference between groups with and without construction-project experiences, relates to the procedures for achieving strategic objectives. This involves understanding the project and organizational characteristics through knowledge accumulation and managing client interactions to ensure successful projects. The Action Research framework facilitates knowledge exchange among clients and practitioners, empowering corporate clients to effectively achieve strategic objectives through group decision-making.